The champions of the Río de la Plata: Football and dictatorship in Argentina and Uruguay - Magalhães, Lívia Gonçalves (Hispania Nova, 2019)
In 1978, Argentina hosted the 11th edition of the Fifa World Cup, under a dictatorial regime that began to suffer internal and external attrition with serious denunciations of human rights violations. In late 1980 and early 1981, Uruguay organized and hosted the Gold Cup of the World Champions which, despite not having the same importance as a World Cup, was endorsed by Fifa, which celebrated the 50th anniversary of its first tournament. Also under dictatorship, the Uruguayans celebrated the victory in the field, just like the Argentines two years before, and saw both the organization and the conquest involved in the official discourse of the regimes. From the analysis of the two events and two victories, we intend to reflect about the relations between soccer and authoritarianism in Argentina and Uruguay, as well as questioning the disputes and the memorialistic speeches that associate sport and dictatorship.
Keywords: Argentina; Uruguay; football; dictatorship; memory ruption